2013
DOI: 10.2478/ijame-2013-0065
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady hydromagnetic couette flow due to ramped motion of one of the porous plates

Abstract: An unsteady flow formation in Couette motion of an electrically conducting fluid subject to transverse magnetic field has been analyzed in the presence of suction/injection through the porous plates when one of the porous plates is in ramped motion. It is assumed that the porous plates are uniformly permeable and the fluid is entering the flow region through one of the porous plates at same rate as it is leaving through the other porous plate. The resulting boundary value problem has been solved exactly under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…L[U(Y,T)]=trueU̅(Y,s)=0Ufalse(Y,Tfalse)esTdT for s>0, as used by Jha and Jibril 15 then the equations in Laplace domain is obtained as: d2trueU¯dY2italicRedtrueU¯dYstrueU¯=trueF¯(s), T>0-0.25em:{leftUtrue¯=0atY=0,Utrue¯=0atY=1, trueF¯(s)=L(F(T))=[1exp(sT0)]s2T0,where s is the Laplace parameter.…”
Section: Mathematical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…L[U(Y,T)]=trueU̅(Y,s)=0Ufalse(Y,Tfalse)esTdT for s>0, as used by Jha and Jibril 15 then the equations in Laplace domain is obtained as: d2trueU¯dY2italicRedtrueU¯dYstrueU¯=trueF¯(s), T>0-0.25em:{leftUtrue¯=0atY=0,Utrue¯=0atY=1, trueF¯(s)=L(F(T))=[1exp(sT0)]s2T0,where s is the Laplace parameter.…”
Section: Mathematical Analysismentioning
confidence: 99%
“…The gradual flow of an electrically conducting, incompressible and viscous, fluid subject to a transverse magnetic field, in the space between two infinite parallel plates due to the ramped motion of the bottom plate was considered by Jha and Jibril. 15 Chandran et al 16 considered the unsteady natural convection flow of an incompressible viscous fluid near a vertical plate with ramped wall temperature. An analysis of the effects of ramped wall temperature and species concentration was carried out on natural convection flow with the Dufour effect, in the space between two parallel plates.…”
Section: Introductionmentioning
confidence: 99%
“…A study on the unsteady hydromagnetic Couette flow through a porous channel, caused by the ramped motion of one of the porous plates was carried out. It was assumed that the horizontal channel was formed by two porous plates of uniform permeability, where suction and injection occur at the same rate [6]. Authors in [7] analyzed the transitory free convection and mass transfer flow of an incompressible fluid through a vertical channel when the Dufour effect is present.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the effects of the suction on velocity are dependent highly on the viscosity parameter. The study of hydromagnetic Couette flow due to ramped motion of one of the porous plates [15] is also examined. For their study, observations were made that the existence of the injection parameter causes the velocity to increase and with the suction parameter, the velocity decreases at the moving porous plate.…”
Section: Introductionmentioning
confidence: 99%